SISTEM PAKAR MENDIAGNOSIS PENYAKIT RHINOSINUSITIS DENGAN MENGGUNAKAN METODE NAÏVE BAYES - Muhammad Hafist Khalaf; Herlina Latipa Sari; Jhoanne Fredricka (Jurnal Media Infotama, 2024)
Rafflesia Hospital Is One Of The Private Public Hospitals In Bengkulu City, And Is Supported By Specialist Doctors And Other Supporting Medical Facilities. One Of Them Is The Rhinosinusitis Service. Rhinosinusitis Is Inflammation Of The Mucosa Or Mucous Membrane Of The Nose And Sinuses. Rhinosinusitis Is Caused By All Conditions That Result In Obstruction Of The Flow Of Mucus From The Sinuses To The Nasal Cavity. Due To The Large Number Of Patients With Rhinosinusitis And Not Being Comparable To The Available Medical Personnel, There Is Limited Time For Patients To Consult And Receive Services At Rafflesia Hospital. The Expert System For Diagnosing Rhinosinusitis Using The Naïve Bayes Method Can Be Accessed Online With Internet Access Via The Web Link Http://Rhinosinusitis.Yms.My.Id/.This Expert System Application Was Created Using The PHP Programming Language And Mysql Database. In The Application, The Naive Bayes Method Has Been Applied Which Is Used To Trace Rhinosinusitis Based On The Symptoms Experienced By The Patient. The System Successfully Displays The Expert System Application Page And Can Assist In Diagnosing Rhinosinusitis, By Providing Consultation Directions Starting From Entering Symptoms To Obtaining Consultation Results And Solutions Provided To Treat The Disease. Based On The Results Of The Tests That Have Been Carried Out, It Can Be Concluded That The Expert System Application For Diagnosing Rhinosinusitis Using The Naive Bayes Method Is Running Well, As Shown By The Expert System Application For Diagnosing Rhinosinusitis Using The Naive Bayes Method That Can Be Easily Used By Users.